Pemanfaatan Lampu Pijar untuk Pencahayaan Buatan pada Photovoltaics sebagai Alternatif PLTS di Laboratorium Energi Terbarukan - Warsono, Warsono; Sunardi, Sunardi (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
This research was conducted to address the challenges of conducting solar panel practicum in the Energy Engineering laboratory during cloudy or rainy weather by developing a simulation module for solar panel experiments using incandescent lamps as the light source. The testing and analysis revealed that solar panel efficiency is higher under sunlight (5.64% at 504 W/m²) compared to incandescent lamps (5.04% at 500 W/m²), with a more pronounced efficiency drop under lamp lighting due to rising temperatures. When temperatures exceed 40°C, a significant decline in efficiency occurs, with rates of 0.106/°C for the lamp and 0.093/°C for sunlight. The solar panel simulation module using incandescent lamps can serve as a practical solution for conducting experiments during overcast or rainy conditions. Keywords: Solar panels, Incandescent lamps, PLTS practicals